1999
DOI: 10.1074/jbc.274.25.17417
|View full text |Cite
|
Sign up to set email alerts
|

Brefeldin A Inhibited Activity of the Sec7 Domain of p200, a Mammalian Guanine Nucleotide-exchange Protein for ADP-ribosylation Factors

Abstract: A brefeldin A (BFA)-inhibited guanine nucleotide-exchange protein (GEP) for ADP-ribosylation factors (ARF) was purified earlier from bovine brain cytosol. Cloning and expression of the cDNA confirmed that the recombinant protein (p200) is a BFA-sensitive ARF GEP. p200 contains a domain that is 50% identical in amino acid sequence to a region in yeast Sec7, termed the Sec7 domain. Sec7 domains have been identified also in other proteins with ARF GEP activity, some of which are not inhibited by BFA. To identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 30 publications
(42 reference statements)
4
31
0
Order By: Relevance
“…PDE3A depletion did not alter total ARF1, 5, or 6, but recovery of active ARF1 was significantly lower, whereas amounts of active ARF5 (class II) and ARF6 (class III) were unchanged. These results, and previous data (8,27), confirm a specificity of endogenous intracellular BIG1 and BIG2 for class I ARFs, despite a sometimes apparent lack of ARF specificity of GEP activity of the highly conserved Sec 7 domains from different GEPs when assayed in vitro (28).…”
Section: Discussionsupporting
confidence: 74%
“…PDE3A depletion did not alter total ARF1, 5, or 6, but recovery of active ARF1 was significantly lower, whereas amounts of active ARF5 (class II) and ARF6 (class III) were unchanged. These results, and previous data (8,27), confirm a specificity of endogenous intracellular BIG1 and BIG2 for class I ARFs, despite a sometimes apparent lack of ARF specificity of GEP activity of the highly conserved Sec 7 domains from different GEPs when assayed in vitro (28).…”
Section: Discussionsupporting
confidence: 74%
“…7c) as observed in the presence of Arf1[T31N] (Fig. 6A, c1-c4), suggesting that, as in animal cells, Arf1 may play a role in the trafficking of H ϩ -ATPase:GFP to the plasma membrane through a BFA-sensitive factor (Sata et al, 1998;Morinaga et al, 1999).…”
Section: Arf1[t31n] May Cause Fusion Of the Golgi Membranes To The Ermentioning
confidence: 70%
“…In animal cells, BFA and the dominant negative mutant of Arf1 have been shown to have similar effects on intracellular trafficking (Sata et al, 1998;Morinaga et al, 1999). BFA has also been shown to inhibit intracellular trafficking in plant cells (Gomez and Chrispeels, 1993;Boevink et al, 1999).…”
Section: Arf1[t31n] May Cause Fusion Of the Golgi Membranes To The Ermentioning
confidence: 99%
“…A candidate is BFA, which inhibits vesicular traffic from the Golgi apparatus by slowing GDP-GTP exchange on ADPribosylation factors (ARF); the latter are targets of GEFs for ARF that are structurally related to Epac, although they are not activated by cAMP (Morinaga et al, 1996(Morinaga et al, , 1999Chardin and McCormick, 1999). We found that BFA also antagonizes 8-CPT action on synaptic transmission, presumably by similarly blocking a downstream action of Epac.…”
Section: A New Epac Antagonistmentioning
confidence: 99%